2002
DOI: 10.1002/pola.10288
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of model linear tetrablock quaterpolymers and pentablock quintopolymers of ethylene oxide

Abstract: Multiblock copolymers of ethylene oxide, with four and five different blocks, were synthesized by the sequential anionic polymerization of styrene, isoprene, 2‐vinyl pyridine, t‐butyl methacrylate, and ethylene oxide with benzyl potassium as an initiator. The monomer sequence was based on the relative nucleophilicity of the active centers. Characterization of the multiblock copolymers by size exclusion chromatography (with refractive‐index and UV detectors), membrane osmometry, and NMR spectroscopy confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…27,36À41 Furthermore, the synthesis of polyisoprene (PI)-b-P2VP-b-poly(ethylene oxide) (PEO), PI-b-P2VP-b-P t BMA, and even a particular PI-b-P2VP-b-P t BMA-b-PEO was reported by Hadjichristidis et al 42,43 Needless to say, the corresponding triblock and tetrablock polymers having block segments different in sequential order cannot be synthesized by changing the sequential addition order of monomers.…”
Section: ' Introductionmentioning
confidence: 90%
“…27,36À41 Furthermore, the synthesis of polyisoprene (PI)-b-P2VP-b-poly(ethylene oxide) (PEO), PI-b-P2VP-b-P t BMA, and even a particular PI-b-P2VP-b-P t BMA-b-PEO was reported by Hadjichristidis et al 42,43 Needless to say, the corresponding triblock and tetrablock polymers having block segments different in sequential order cannot be synthesized by changing the sequential addition order of monomers.…”
Section: ' Introductionmentioning
confidence: 90%
“…The morphologies and the phase diagrams for AB diblock copolymer, linear ABC triblock copolymer, even ABC 3-miktoarm copolymer are intensively studied both theoretically and experimentally [1e16]. The more complicated block copolymer, such as those of linear ABCA [17], and ABCD [18e22], ABCDE [20] types and even ABCD 4-miktoarm star quarterpolymer [23] (A is polystyrene, B is polybutadiene, C is polyisoprene, and D is poly(4-methylstyrene)) are synthesized. After that, Dotera et al [24,25] found that a monodisperse symmetric ABCD star block copolymer melt undergoes a microphase separation by using Monte Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that phenyl vinyl sulfoxide [67] and alkyl isocyanate monomers [43][44][45][46] undergo living anionic polymerization to result in interesting polymers, poly(4-phenyl vinyl sulfoxide), convertible to conductive rod-like poly(acetylene) and poly(alkyl isocyanate)s with helical conformation. These specialty functional polymers may also be used, at least to a certain extent, in the linking methodology to synthesize block polymers containing blocks with rod-like and helical conformations.…”
Section: Future Outlookmentioning
confidence: 99%
“…The first synthetic example was an ABCD tetrablock quaterpolymer of PS-b-PI-b-P2VP-b-poly(ethylene oxide) (PEO), which was synthesized by the sequential addition of styrene, isoprene, 2VP, and EO to benzyl potassium as the initiator [43]. The polymerizations of the first three monomers were carried out in THF at −78 °C for 1, 1, and 0.5 h, respectively, while the final polymerization of EO was performed in THF at 50 °C for five days.…”
Section: Synthesis Of Block Polymers By Sequential Polymerizationmentioning
confidence: 99%